2022
DOI: 10.3390/nu14214587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epidermal Growth Factor in Human Milk and Maternal Diet on Late-Onset Breast Milk Jaundice: A Case-Control Study in Beijing

Abstract: Breast milk is crucial in the development of late-onset breast milk jaundice (BMJ), possibly due to the composition of breast milk and the lactating mother’s diet. To explore the possible nutritional pathogenesis of late-onset BMJ, we investigated the lactation diet and collected breast milk by following the 42-day postpartum mother–infants pairs in Beijing and a total of 94 pairs were enrolled. The macronutrient content of breast milk was measured, and the epidermal growth factor (EGF) content in breast milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 26 publications
0
22
0
7
Order By: Relevance
“…A total of 12 unique studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] were included in this review, all of which were observational in nature, and the study characteristics are shown in Table 1 . The included studies were dated between 1964 [ 43 ] and 2022 [ 36 ], with the majority conducted prior to the 2000s [ 32 , 34 , 35 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 unique studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] were included in this review, all of which were observational in nature, and the study characteristics are shown in Table 1 . The included studies were dated between 1964 [ 43 ] and 2022 [ 36 ], with the majority conducted prior to the 2000s [ 32 , 34 , 35 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 unique studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] were included in this review, all of which were observational in nature, and the study characteristics are shown in Table 1 . The included studies were dated between 1964 [ 43 ] and 2022 [ 36 ], with the majority conducted prior to the 2000s [ 32 , 34 , 35 , 38 , 39 , 40 ]. Nearly half of the included studies were conducted in Turkey ( n = 6) [ 33 , 34 , 37 , 38 , 41 , 42 ], and the rest were from six other countries, including China [ 36 ], Italy [ 40 ], Switzerland [ 32 ], the United Kingdom [ 35 ], and the United States of America [ 39 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar interpretation of findings were published in a more recent retrospective case-control study of 324 infants in China (Yang et al, 2022). However, a systematic review on human milk constituents and the development of “breast milk jaundice” states that “breast milk jaundice” is likely multifactorial, since no single constituent of human milk could yet explain all human milk jaundice cases observed (Gao et al, 2023). It is unclear, therefore, why these epidemiological studies interpret human milk as a causal risk factor for infant jaundice based solely on the risk differences between breastfed and formula fed groups.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends exclusive breastfeeding of infants for the first 6 months of life, but among the factors leading to interruption or early termination of breastfeeding, BMJ is one of the main factors ( 5 ). Notably, in recent years, with the popularization of breastfeeding in China, more and more infants are found to develop BMJ in the clinic, and BMJ is gradually becoming the leading cause of neonatal jaundice ( 15 ).…”
Section: Bmj Influences Breastfeedingmentioning
confidence: 99%
“…Interrupting breastfeeding to treat breast milk jaundice (BMJ) has long been controversial and may increase the risk of early termination of breastfeeding ( 4 ). In the community, the impact of neonatal BMJ on reduced breastfeeding and vaccination rates has been widely observed, which may resulting in adverse consequences for infant growth and disease prevention, even though clinicians generally advise continuing exclusive breastfeeding during BMJ ( 5 ). Therefore, clarifying the pathogenesis of BMJ is of great importance to prevent the occurrence of these adverse effects ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%